Analysis of Factors that Influence Investment Decisions with Financial Literacy as a Moderating Variable - Tia Mahrurotul Fikriyah; Dwi Suhartini (Indonesian Journal of Business Analytics, 2023)
Investment is an important driving factor in a country's economic growth. However, in making investment decisions, factors such as fundamental analysis, technical analysis, psychological factors, and financial literacy can influence the results of investment decisions. Therefore, this study aims to analyze these factors and their relationship with investment decisions. This study uses a quantitative method with a descriptive approach. The research subjects were students of the East Java "Veteran" National Development University. Data is collected through a questionnaire that measures the level of influence of these factors on investment decisions, with financial literacy as a moderating variable. The results show that fundamental analysis has limitations because it depends on limited data. Technical analysis also has limitations because it relies on limited historical data and is vulnerable to sudden market changes. Psychological factors, such as self-confidence and risk tolerance, also influence investment decisions. However, financial literacy has only a limited impact on moderating the relationship between these factors and investment decisions. In making investment decisions, factors such as fundamental analysis, technical analysis, and psychological factors play an important role. Although financial literacy can assist in understanding basic financial concepts, its influence on these factors is limited. Therefore, increasing financial literacy among students and the millennial generation is expected to increase their understanding of managing risk and making wiser investment decisions.